Training On the Implementation of Independent Curriculum Learning for Teachers in Sekolah Indonesia Jeddah - Kusumantoro, Kusumantoro; Setiaji, Khasan; Nurkhin, Ahmad; Raharjo, Teguh Hardi Raharjo (Universitas Negeri Semarang, 2023)
Rendahnya pengetahuan dan keterampilan guru menjadi faktor utama belum terimplentasikannya Kurikulum Merdeka di Krisis pembelajaran di Sekolah Indonesia Jeddah (SIJ). Tidak adanya program guru penggerak dan sekolah penggerak di SIJ disinyalir menjadi penyebab guru masih kesulitan dalam menyelenggarakan proses pembelajaran yang sesuai dengan kurikulum merdeka. Sehingga, melalui kegiatan pengabdian ini diharapkan mampu membekali pengetahuan dan keterampilan guru SIJ dalam mengimplementasikan kurikulum merdeka pada proses pembelajaran yang dilakukan. Kegiatan ini terlaksana pada hari Sabtu 9 September 2023 secara daring dengan peserta 7 guru di Sekolah Indonesia Jeddah (SIJ). Kegiatan ini berlangsung dengan lancar dengan antusiase peserta dalam diskusi. Berdasarkan hasil evalusi ditahap akhir menunjukan bahwa kegiatan ini mampu meningkatakan pemahaman dan kesiapan guru dalam meningkatkan kesiapan mengimplementgasikan kurikulum merdeka dalam pembelajaran. The low level of knowledge and skills of teachers is the main factor in the failure to implement the Independent Curriculum in the learning crisis at Sekolah Indonesia Jeddah (SIJ). The absence of a driving teacher program and driving schools at SIJ is allegedly the reason why teachers still have difficulties in carrying out learning processes that are in accordance with the independent curriculum. So, through this service activity it is hoped that SIJ teachers will be able to equip the knowledge and skills in implementing the independent curriculum in the learning process carried out. This activity was held online on Saturday 9 September 2023 with 7 teachers at the Jeddah Indonesian School (SIJ) participating. This activity went smoothly with enthusiastic participants in the discussion. Based on the evaluation results at the final stage, it shows that this activity is able to increase teachers' understanding and readiness in increasing their readiness to implement the independent curriculum in learning.